Hume’s Theory of Causation: Is There More Than One? - Hill, James (Teorie vědy / Theory of Science, 2011)
It is traditionally assumed that there is only one theory of causality in Hume's writings. In this article it is shown that we can distinguish between an early and mature theory. It is argued that the mature theory, strongly influenced by Newton's physics, accords with the New Hume (sceptical realist) interpretation by asserting that real causal relations are not accessible to the human mind.